2004
DOI: 10.1111/j.1527-3458.2004.tb00011.x
|View full text |Cite
|
Sign up to set email alerts
|

ABT‐089: Pharmacological Properties of a Neuronal Nicotinic Acetylcholine Receptor Agonist for the Potential Treatment of Cognitive Disorders

Abstract: ABT-089 [2-methyl-3-(2-(S)-pyrrolidinylmethoxy)pyridine dihydrochloride salt] is a selective neuronal nicotinic receptor (NNR) modulator with cognitive enhancing properties in animal models of cognitive functioning. Amongst NNR subtypes, ABT-089 shows selectivity for the cytisine binding site on the á 4 â 2 receptor subtype as compared to the á-bungarotoxin (á-BgT) binding sites on the á 7 and á 1 â 1 äã receptor subtypes. In functional in vitro electrophysiological and cation flux assays, ABT-089 displays dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 34 publications
1
57
0
2
Order By: Relevance
“…ABT-089 [2-methyl-3-[2(S)-pyrrolidinylmethoxy]pyridine; structure in Lin et al, 1997] is a selective partial agonist for a4b2* receptors with high selectivity for a4a5b2 and activity at a6b2* receptors (Rueter et al, 2004;Marks et al, 2009). ABT-089 has been rigorously studied as a treatment of cognitive disorders and has been used successfully in patients with Alzheimer's disease and attention deficit disorder, with few unintended side effects Rueter et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…ABT-089 [2-methyl-3-[2(S)-pyrrolidinylmethoxy]pyridine; structure in Lin et al, 1997] is a selective partial agonist for a4b2* receptors with high selectivity for a4a5b2 and activity at a6b2* receptors (Rueter et al, 2004;Marks et al, 2009). ABT-089 has been rigorously studied as a treatment of cognitive disorders and has been used successfully in patients with Alzheimer's disease and attention deficit disorder, with few unintended side effects Rueter et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The cognition enhancer ABT-089 (Decker et al, 1997) was classified as a ␣4␤2*-selective nAChR agonist based on high affinity and selectivity to this receptor subtype (Sullivan et al, 1997). Moreover, partial agonism at this receptor was deduced based on the relatively low efficacy of ABT-089, when compared with nicotine, in stimulating [ 86 Rb ϩ ] efflux from cells expressing human ␣4␤2* nAChRs (Sullivan et al, 1997;Rueter et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other partial agonists, ABT-089 demonstrated a more advantageous safety profile in preclinical species than full agonists (Rueter et al, 2004), consistent with the notion of an increased safety margin of partial agonists relative to full agonists (Hogg and Bertrand, 2007). However, nicotinic compounds may require high doses to achieve clinical efficacy that, unfortunately, elevates the potential for adverse effects.…”
Section: Introductionmentioning
confidence: 58%
“…Previous radioligand binding studies have shown that ABT-089 interacts with high affinity at the ␣ 4 ␤ 2 * subtype of both rodent and human nAChRs in which affinities were measured by displacement of specific [ 3 H](Ϫ)-cytisine binding from rat brain membranes (K i ϭ 17 nM) and from human ␣ 4 ␤ 2 * nAChRs stably expressed in a human embryonic kidney cell line (Rueter et al, 2004). Results from our in vivo imaging study show that ABT-089 displaces […”
Section: Discussionmentioning
confidence: 99%